Ketidaksesuaian Antara Pemenuhan Jaminan Garansi Dengan Garansi Yang Diperjanjikan - Nadhira Yasmine Faluni; Siti Nurlaeli Al Fadilah; Dara Berlianti; Muhammad Ageng Cahyo Sambodo; Anak Agung Gede Divpra Kusuma Aryuntra; Farahdinny Siswajanti (Universitas Sains dan Teknologi Komputer, 2024)
The rapid growth of technology in both conscious and unconscious man has depended on technology in all aspects of his life. Because technology items are quite expensive and prone to damage, a guarantee (guarantee) becomes an attraction for consumers so that at least the expensive items they have bought are protected within a certain time and guaranteed quality. However, often in fulfillment of the warranty does not match the warranty promised by the business operator when purchasing the product. This article is intended to share information with the public about the warranty and protection, and the ways or steps that the public can take when faced with the issue of mismatches between warranty fulfillment and the promised warranty. In this research we used a normative juridical study methodology with library information collection procedures. Regarding this problem, the government has made a legal product, namely Law Number. 8 Year 1999 on consumer protection in which a person controls a warranty, which, if the public may be harmed by such discrepancies, he or she has the right to bring this to law through the Consumer Dispute Resolution Agency or through a public court.